Armenia : Sustainable and Strategic Decision Making in Mining - World Bank (Washington, DC, 2014)
This paper aims to inform Armenia's policy dialogue on environmental and social issues in the mining sector. The paper is based on the premise that for the mining sector to have positive, long-term impacts in Armenia, it is necessary to take into consideration the short- and long-term environmental and social impacts of the sector and to promote strategic planning and efficient management of natural resources. The mining sector in Armenia has yet to adopt global best practices in this sector, and this paper aims to provide guidance on some of the mechanisms that can be adopted to improve the governance and overall impact of mining in the country. The document is structured as follows: chapter one presents an introduction to this thematic paper. Chapter two provides an overview of the mining sector in Armenia, including its underpinning institutional and regulatory framework. It also singles out policy gaps and regulatory inconsistencies that need to be addressed. Chapter three presents some useful lessons of the application of SESA as a tool for sustainable planning of mining development in the country. This chapter also compares uses of an SESA versus Environmental Impact Assessments and defines the need and use of CIAs. Chapter four describes the principles of valuation of natural capital as a means to complement traditional cost-benefit analysis and comparisons of development alternatives in the decision-making process. Chapter five looks at the design and implementation of benefit-sharing mechanisms to ensure that the mining activities lead to positive social impacts across the country. Chapter six looks at the process of determining and dealing with the social costs of mining in Armenia. Chapter seven provides a series of conclusions and recommendations as well as implementation challenges that would summarize the application of such recommendations in present-day Armenia and its mining sector.